Innovation management: work with mistakes (Journal of Economic Research & Business Administration, 2015)
Innovative development of economy is considered today by many countries as one of the main ways of economic growth, ensuring competitiveness. The most discussed questions of innovations in the Republic of Kazakhstan are: institutes, finance, regulation, shots, technologies, intellectual property rights. Such rather aspect of research can become the integral element in the mechanism of realization of Strategy of industrial and innovative development of Kazakhstan. The article deals with problems concerning the industrial-innovative development of Kazakhstan.
Keywords: innovation; innovative economy; commercializing of ideas; venture funds; technoparks; innovative infrastructure